Time-motion analysis of youth Olympic taekwondo combats - Tornello, F.; Capranica, L.; Chiodo, S.; Minganti, C.; Tessitore, A. (The Journal of Strength and Conditioning Research, 2013)
This study aimed to analyze the time-motion structure of combat phases (fighting: F, nonfighting: NF, and stoppage time: ST) during semifinal and final matches (three 1.5-minute rounds, with 1-minute rest in between) of the 2010 Italian Taekwondo Cadet (age 13-14 years) Championship (adolescent boys, n = 40; adolescent girls, n = 28) in relation to gender (adolescent boys and girls) and grouped weight division (light, middle, and heavy) of athletes. Regardless of gender, grouped weight division, round, and tournament stage, differences (p < 0.001, effect size range: 1.92-3.02) emerged for frequency of occurrence of combat phases (F: 42.4 ± 0.5%; NF: 44.5 ± 0.7%; ST: 13.1 ± 0.9%) and their mean duration (F: 2.8 ± 1.0 seconds; NF: 6.5 ± 1.8 seconds; ST: 13.7 ± 5.0 seconds). A 1:2 F to NF ratio was found, whereas a 1:3 ratio emerged when F was considered in relation to the sum of NF and ST. During F phase, 5 ± 1 tactical movements and 4 ± 1 technical exchanges were performed, lasting 0.6 ± 0.1 seconds and 0.7 ± 0.1 seconds, respectively. These findings mirrored the intermittent nature of youth combat, characterized by a high occurrence of tactical movements and technical exchanges during F phase. The lack of differences for round and tournament stages indicates a limited tactical capability of young athletes in adopting specific match strategies, independently from gender and weight divisions of the athletes. To prepare young athletes to handle the technical-tactical demands of the match, coaches could include 7-9 circuit stations of specific taekwondo sequences of attack and counter attack techniques.